Are sexual health survey items understood as intended by African and Asian migrants to Australia? Methods, results and recommendations for qualitative pretesting - Vujcich, Daniel; Roberts, Meagan; Brown, Graham; Durham, Jo; Gu, Zhihong; Hartley, Lisa; Lobo, Roanna; Mao, L.; Moro, P.; Mullens, A.; Offord, B.; Oudih, E.; et al. (BMJ Journals, 2021)
Introduction: More research and policy action are needed to improve migrant health in areas such as sexual health and blood-borne viruses (SHBBV). While Knowledge, Attitudes and Practice Surveys (KAPS) can inform planning, there are no SHBBV KAPS suitable for use across culturally and linguistically diverse contexts. This study pretests one instrument among people born in Sub-Saharan Africa, South-East and North-East Asia living in Australia.